Busan Geoje Fixed Link. (April 2022) - van Westendorp, Peter; Louis, Bard; Jackson, Peter
Highlights: Immersed tunnel in a seismic sensitive area consisting of 18 tunnel elements. Total length of 3.6 km, maximum depth of the tunnel is 48 m below sea level. Founded on a sea bottom varying from weak marine clay to bedrock. Long term wave-weather forecast system, 10 cm wave height accuracy 4 days in advance. Fine positioning of TE's by an External Positioning System (EPS). Abstract: The Busan Geoje Fixed Link project is one of the landmark projects in South Korea, providing a road connection between Gaduk and Geoje Island near to the city of Busan at the Southern tip of the Korean peninsula. The project consists of two Cable Stayed Bridges, an Immersed Tunnel, rock tunnels and it has a total length is over 8 km. This paper will focus on the immersed tunnel part of the link and the particular challenges that the project faced in designing and constructing the tunnel, these challenges required a significant evaluation in immersed tunnel technology. The tunnel consists of 18 tunnel elements and has a total length of 3.6 km. The tunnel location was characterised by the following conditions: a large depth, maximum depth of the tunnel is 48 m below sea level. the tunnel is located in a seismic sensitive area. the tunnel is founded largely on weak marine clay, but parts also on bedrock. part of the tunnel was constructed on a sub sea embankment which is also founded on a weak marine clay. the tunnel has been constructed in a location that is facing to the Sea of japan and is exposed to a severe wind and wave environment with large long period swell waves present for part of the year. Because for only a few months a year the wave- and weather circumstances were suitable for immersion, extensive numerical and physical model tests were carried out to predict the behaviour of the immersion system for the expected conditions. These model tests were used to determine the wind and wave climate that the immersion system could cope and a go, no-go range of conditions. Additionally, an accurate, sophisticated short and long term wave and weather forecast system was developed. This system enabled forecasts to be made within a 10 cm wave height accuracy, for periods leading up to the element transport and immersion operations which allowed the immersion operations to be possible within acceptable risks. The tunnel elements (TE) were built in batches in a pre-cast yard (PC). After inundation of the dock the elements were transported to a mooring location close to the PC-yard for fitting out and to wait for favourable immersion weather. The elements were immersed using two catamaran pontoons and placed in a previous dredged trench on the sea bed. A taut mooring configuration was used in order to reduce the wave influenced motions to a minimum. Anchor points were created by pre-installed plate anchors. Due to the total length and installation depth of the tunnel the traditional survey systems using towers and total stations were not suitable. Therefore new survey methods were developed, these included a tautwire system and an Ultra Short Base Line (USBL) acoustic system were used for the positioning of the elements during the immersion operation. Fine positioning of the TE's under swell wave influence was done using a special designed External Positioning System (EPS) and placed on the pre-laid screeded gravel bed.